KUALITAS PELAYANAN RAWAT INAP PUSKESMAS DINOYO KOTA MALANG - Oktaviana Bibu (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Public service is a service that is very important for the community and a top priority for theimplementation of public services. This study aims to determine the quality of inpatient services at DinoyoHealth Center. This research method uses a type of qualitative research. Data obtained from primarydata and secondary data. Data collection uses interviews, observation and documentation. The results ofthe study show that the services provided to general patients and health BPJS patients at the DinoyoHealth Center are of quality seen from: reliability, responsiveness / responsiveness, assurance /assurance, empathy / empathy. Supporting factors for quality inpatient services are the attitude ofemployees who are polite and courteous, simplicity of flow and affordable costs. However, there are stillinhibiting factors that need to be improved, namely the lack of supporting facilities and infrastructure,such as: the seats at the drug withdrawal counters are lacking, the wifi network is slow, and the lack ofstaff that is not suitable for the number of patients.Keywords: Service Quality, Inpatient Care, Center ServicesAbstrak: Pelayanan publik adalah Pelayanan yang sangat penting untuk masyarakat dan menjadiprioritas utama bagi penyelenggaraan pelayanan publik. Penelitian ini bertujuan untuk mengetahuikualitas pelayanan Rawat Inap di Puskesmas Dinoyo. Metode penelitian ini menggunakan jenispenelitian kualitatif. Pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Teknikpenentuan informan menggunakan purposive sampling. Analisis data menggunakan reduksi data,penyajian data dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi teknik. Hasilpenelitian menunjukkan bahwa pelayanan yang diberikan kepada pasien umum dan pasien BPJSkesehatan di Puskesmas Dinoyo sudah berkualitas yang dilihat dari: kehandalan (reliability), dayatanggap (responsiveness), jaminan (assurance), empati (empathy). Faktor pendukung pelayanan rawatinap yang berkualitas adalah sikap pegawai yang ramah sopan dan santun, kesederhanaan alur dan biayaterjangkau. Namun, masih ada faktor penghambat yang perlu diperbaiki yaitu kurangnya sarana danprasarana penunjang, seperti: kursi pada loket pengambilan obat yang kurang, jaringan wifi yang lambat,serta kurangnya jumlah pegawai .Kata Kunci: Kualitas Pelayanan, Rawat Inap, Pelayanan Puskesmas